2019
DOI: 10.1021/acs.macromol.9b02281
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Poly(ethylene-vinyl acetate) with Improved Properties through Dynamic Cross-Linking

Abstract: The low properties of recycled polymers associated with high cost of recycling hinder development of the thermoplastic recycling industry. Dynamic cross-linking of recycled thermoplastics with the formation of vitrimers enables superior mechanical properties, good reprocessability, and superior chemical and environmental resistance. Herein, a poly(ethylene-vinyl acetate) (EVA) vitrimer was formed by cross-linking with triethyl borate with the catalyst (bis-(acetylacetonato)dioxomolybdenum(VI)). The resultant E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…The molecular weight between successive crosslinks, M e , can be obtained from G p ≅ ρRT/M e , where G p is the storage modulus of the rubbery plateau at temperature T and ρ is the polymer density. [ 40 , 41 , 42 ] A higher rubbery plateau modulus points out to higher crosslinking density. Thus, from the results we can conclude that the V‐3 sample has the highest crosslinking degree.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular weight between successive crosslinks, M e , can be obtained from G p ≅ ρRT/M e , where G p is the storage modulus of the rubbery plateau at temperature T and ρ is the polymer density. [ 40 , 41 , 42 ] A higher rubbery plateau modulus points out to higher crosslinking density. Thus, from the results we can conclude that the V‐3 sample has the highest crosslinking degree.…”
Section: Resultsmentioning
confidence: 99%
“…However, these benefits come at the cost of dramatically impeded reprocessability via conventional thermomechanical methods . To circumvent the static nature of thermosets without entirely compromising their stability, network structures containing dynamic linkages have been developed to permit cross-link exchange and macroscopic flow. , In particular, vitrimers have shown great promise in terms of material properties and reprocessability. , Thus far, most research has focused on the exploration of different cross-link exchange chemistries, catalyst systems, and network structures. However, a critical hurdle for the application of vitrimers lies in the translation from the academic laboratory to industrially relevant materials and procedures. , For example, vitrimer materials have been developed using readily available, inexpensive monomers or postpolymerization modification from commercially available polymers. ,, Our group recently prepared vitrimeric poly­(methyl methacrylate) mimetics that exhibited superior thermal and solvent stability while maintaining reprocessability through amine exchange of vinylogous urethane (VU) cross-links . Moreover, we reported that the phase separation present in vitrimers derived from block copolymers leads to enhanced resistance to macroscopic deformation as compared with networks prepared from statistical copolymers of identical compositions .…”
mentioning
confidence: 99%
“…The boric acid groups, which are bound to PLA or ESO, readily form boroxine, 20 , 23 while borate ester can be formed by the reaction between boric acid groups and the hydroxyl groups of PLA or those produced by the opening of the rings in epoxy groups. 22 The possible links by forming boroxine or borate ester in the blend can enhance the interactions between PLA and ESO, which helps to improve the compatibility between them. Moreover, these links allow for the extension of PLA chains to compensate for the decrease in their M n due to thermal degradation.…”
Section: Resultsmentioning
confidence: 99%